(untitled) (Experimental biology, 2015)
In cadmium intoxication in the blood and lymphatic vessels rats contractive activity was sharply depressed. The data obtained indicates that artificial sorbent SUMS-1 acts as purificator, relaxing the influence of ions of cadmium. From the abovementioned one can conclude that in condition of chronic experimental cadmium intoxication it is possible to use the methods of artificial detoxication we would presented.